30 Calf Performance and Sex Ratios in Second Generation Reciprocal Nellore-angus Crosses. (8th October 2021) - Mickey, Dana; Sanders, James; Riley, David G; Herring, Andy D
Abstract: The objectives of this study were to analyze calf weight and sex distribution differences in reciprocal F2 Nellore-Angus calves (n = 559) born 2010–2015 and calves out of these F2 females through 4 yr age (n = 469) born 2012–2018. The F2 animals were produced by 4 F1 parent type combinations from Nellore-sired (NA) vs. Angus-sired (AN) sires and dams. Weight traits were analyzed using mixed models, and sex distribution was analyzed through PROC GLIMMIX in SAS. Sire type and dam type affected birth weight (P < 0.05) but not weaning weight of the F2 calves. However, the interaction between sire type and dam type accounted for weaning weight differences (P = 0.038). Birth weight averaged 3.5 kg heavier from NA vs. AN sires, and 2.4 kg heavier from NA vs. AN dams. Weaning weight displayed a different pattern than observed in birth weight with the heaviest calves being NAAN (224.5 ± 3.7 kg) and lightest being ANAN (215.9 ± 3.9 kg). Sire type accounted for important variation (P = 0.036) in the calf sex distribution at birth among F2 calves. Percentage males at birth exceeded the expected ratio for NA-sired calves (66.6%, n = 168) but not for AN-sired calves (49.9%, n = 105). The sire and dam type main effects in the F2 females did not influence weight traits or sex distribution in their calves (from predominantly Angus sires). However, the interaction of sire type x dam type x sex showed a trend in birth weight (P = 0.080) and importance for weaning weight (P = 0.010) where only from ANNA and NANA dams were males heavier than females. These results suggest that some of the calf weight reciprocal differences typically observed among F1 Bos indicus-Bos taurus crosses can persist in later generations.